Analysis of the Quality of Administrative Services for Non-Permanent Residents in Sanur Village - Riyastini, Ni Ketut; Ida Ayu Putu Sri Widnyani; Nyoman Dwika Ayu Amrita (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
Non-permanent residence administration is a very important aspect to ensure that every individual living in an area, even temporarily, is still registered and well served. The form of this research is descriptive research with data collection methods using three types of techniques, namely observation methods, interview methods and documentation methods. This research was conducted to find out what the quality of public services in Sanur Village is, what are the obstacles in non-permanent population administration services in Sanur Village, and what efforts are being made to overcome obstacles in Non-permanent Population Administration services in Sanur Village. Based on the research results, it can be concluded that non-permanent population administration services in Sanur Village have variations in terms of reliability and responsiveness. Furthermore, the main obstacles in non-permanent population administration services in Sanur Village include limited number of employees, technical problems such as unstable internet connections, and inconsistencies in service implementation. The local Village Government's efforts to overcome these obstacles are by carrying out continuous innovation and employee training to increase the reliability and responsiveness of services. It is recommended that the use of online media and communication applications be maximized to speed up the administration process and increase service accessibility. In addition, collecting community feedback and regular evaluation of employee performance must be further improved.